Assessment on the Status and Prospects of Goat Farming in Khajura Rural Municipality - Pandey, Rahul; Gautam, Suraj; Panta, Tripti (Journal of Agriculture and Forestry University, 2026)
Goat farming is a key livelihood source in Nepal’s rural areas, yet systematic evidence on its status and constraints at the local municipality level remains limited. This study assessed the current status and future prospects of goat farming in Khajura Rural Municipality, Banke district, conducted from March to June 2025. Using simple random sampling, 95 goat-rearing households were surveyed through semi-structured interview schedules. The study found that semi-intensive farming (88.40%) and crossbred goats (26.34%) were dominant. The three most critical production constraints were inadequate nutrition management (index = 0.83), unavailability of quality breeds (0.80), and market instability (0.78). Economic analysis revealed a benefit-cost ratio of 1.22 and a net profit of NRs. 28,014 per farm, confirming financial viability. Despite limited access to government subsidies (3.15%) and formal training (13.70%), 92.60% of farmers expressed willingness to expand, indicating strong commercialization potential. Targeted policy support, capacity-building interventions, and market stabilization mechanisms are recommended to unlock this potential.